2020
DOI: 10.3892/mmr.2020.11737
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA ZFPM2‑AS1 promotes colorectal cancer progression by sponging miR‑137 to regulate TRIM24

Abstract: Accumulating evidence indicates that long non-coding RNAs (lncRNAs) may serve essential roles during tumorigenesis of colorectal cancer (CRC). The lncRNA ZFPM2-AS1 was observed to be involved in the progression of numerous types of cancer, such as lung adenocarcinoma and cervical cancer. The aim of the present study was to investigate the expression levels and function of ZFPM2-AS1 in CRC. Expression levels of ZFPM2-AS1 in tissue and CRC cells were measured by reverse transcription-quantitative PCR. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Only one (C9orf170) of the six lncRNAs met the criteria for expression validation, co-expression analysis, and survival analysis. Emerging evidence suggests that lncRNAs may have critical effects on cancer progression and development [41,42]. However, there are few reports on the effects of C9orf170 on diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Only one (C9orf170) of the six lncRNAs met the criteria for expression validation, co-expression analysis, and survival analysis. Emerging evidence suggests that lncRNAs may have critical effects on cancer progression and development [41,42]. However, there are few reports on the effects of C9orf170 on diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have demonstrated that dysregulation of lncRNA ZFPM2-AS1 is implicated in the initiation and development of a variety of malignant tumors; lncRNA ZFPM2-AS1 is located at the 8q23 region, an aggregate of cancer susceptibility loci, ( Okamoto et al, 2003 ), and can act as an oncogene to promote HCC cell proliferation, invasion, and metastasis. As discovered by Xiao et al, lncRNA ZFPM2-AS1 can promote colorectal cancer progression by sponging miR-137 to regulate TRIM24 ( Xiao et al, 2021 ). Similarly, LUCAT1 also plays a key role in the progression and metastasis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the elevated levels of another lncRNA FOG family member 2 antisense RNA 1 (ZFPM2-AS1) were demonstrated to be correlated with cell proliferation, migration, and invasion in CRC. The ZFPM2-AS1 acts as competing endogenous RNA (ceRNA) and competitively binds with miR-137 and in turn, upregulates the expression of tripartite motifcontaining 24 (TRIM24) which is a downstream target of miR-137 [135]. Previous studies showed that the upregulation of TRIM24 is associated with increased proliferation and inhibition of apoptosis in CRC cells, Moreover, the knockdown of TRIM24 leads to a decrease in the expression of Bcl-2 and a significant increase in the expression of caspase 3 and PARP [136,137].…”
Section: Intrinsic Apoptosis (Mitochondrial Pathway)mentioning
confidence: 99%